Reprogramming of Adult Peripheral Blood Cells into Human Induced Pluripotent Stem Cells as a Safe and Accessible Source of Endothelial Cells - Simara, Pavel; Tesarova, Lenka; Rehakova, Daniela; Farkas, Simon; Salingova, Barbara; Kutalkova, Katerina; Vavreckova, Eva; Matula, Pavel; Matula, Petr; Veverkova, Lenka; Koutna, Irena (Stem cells and development, 2018)
New approaches in regenerative medicine and vasculogenesis have generated a demand for sufficient numbers of human endothelial cells (ECs). ECs and their progenitors reside on the interior surface of blood and lymphatic vessels or circulate in peripheral blood; however, their numbers are limited, and they are difficult to expand after isolation. Recent advances in human induced pluripotent stem cell (hiPSC) research have opened possible avenues to generate unlimited numbers of ECs from easily accessible cell sources, such as the peripheral blood. In this study, we reprogrammed peripheral blood mononuclear cells, human umbilical vein endothelial cells (HUVECs), and human saphenous vein endothelial cells (HSVECs) into hiPSCs and differentiated them into ECs. The phenotype profiles, functionality, and genome stability of all hiPSC-derived ECs were assessed and compared with HUVECs and HSVECs. hiPSC-derived ECs resembled their natural EC counterparts, as shown by the expression of the endothelial surface markers CD31 and CD144 and the results of the functional analysis. Higher expression of endothelial progenitor markers CD34 and kinase insert domain receptor (KDR) was measured in hiPSC-derived ECs. An analysis of phosphorylated histone H2AX (γH2AX) foci revealed that an increased number of DNA double-strand breaks upon reprogramming into pluripotent cells. However, differentiation into ECs restored a normal number of γH2AX foci. Our hiPSCs retained a normal karyotype, with the exception of the HSVEC-derived hiPSC line, which displayed mosaicism due to a gain of chromosome 1. Peripheral blood from adult donors is a suitable source for the unlimited production of patient-specific ECs through the hiPSC interstage. hiPSC-derived ECs are fully functional and comparable to natural ECs. The protocol is eligible for clinical applications in regenerative medicine, if the genomic stability of the pluripotent cell stage is closely monitored.
Keywords: buněčná diferenciace; regenerativní lékařství; endothelial differentiation; Humans; fyziologická neovaskularizace; Leukocytes, Mononuclear; Induced Pluripotent Stem Cells; peripheral blood mononuclear cells; lidé; Biomarkers; Cells, Cultured; Human Umbilical Vein Endothelial Cells; indukované pluripotentní kmenové buňky; induced pluripotent stem cells; biologické markery; Endothelial Cells; kultivované buňky; endoteliální buňky pupečníkové žíly (lidské); Cell Differentiation; endoteliální buňky; leukocyty mononukleární; fibroblasty; Neovascularization, Physiologic; Regenerative Medicine; Fibroblasts